(untitled) (Research, Society and Development, 2020)
The present work aims to make public current data on the epidemiological picture of measles in Brazilian territory. Measles is a highly contagious virus and difficult to control when there is no previous vaccination, it mainly affects children, but there are also registered cases of measles in other age groups. There was a certain period in which no case of infection was found in Brazil, leading to the conclusion that the disease would be eradicated at that particular moment. However, there is currently a new epidemic gaining momentum, requiring a new approach to epidemiological data. The data were analyzed from epidemiological reports from bulletins and weekly reports available on the Ministry of Health website, through quantitative informational research in 2019. It is hoped through this research to expand the view of the epidemiological picture of measles in the country, thus being able to contribute to the elaboration of public policies aimed at the prevention and control of measles in Brazil, in addition to clarifying society, about the risks caused by this new outbreak of the disease.